Age- and Sex-Specific Trends in Medical Complications After Acute Ischemic Stroke in the United States. (21st March 2023) - Ahmed, Rashid; Mhina, Carl; Philip, Karan; Patel, Smit D.; Aneni, Ehimen; Osondu, Chukwuemeka; Lamikanra, Oluwatomi; Akano, Emmanuel Oladele; Anikpezie, Nnabuchi; Albright, Karen C.; Latorre, Julius G.; Chaturvedi, Seemant; et al.
Abstract : Background and Objectives: To test the hypothesis that the age and sex-specific prevalence of infectious (pneumonia, sepsis, and urinary tract infection [UTI]) and noninfectious (deep venous thrombosis [DVT], pulmonary embolism [PE], acute renal failure [ARF], acute myocardial infarction [AMI], and gastrointestinal bleeding [GIB]) complications increased after acute ischemic stroke (AIS) hospitalization in the United States from 2007 to 2019. Methods: We conducted a serial cross-sectional study using the 2007–2019 National Inpatient Sample. Primary AIS admissions in adults (aged 18 years or older) with and without complications were identified using International Classification of Diseases codes. We quantified the age/sex-specific prevalence of complications and used negative binomial regression models to evaluate trends over time. Results: Of 5, 751, 601 weighted admissions, 51.4% were women. 25.1% had at least 1 complication. UTI (11.8%), ARF (10.1%), pneumonia (3.2%), and AMI (2.5%) were the most common complications, while sepsis (1.7%), GIB (1.1%), DVT (1.2%), and PE (0.5%) were the least prevalent. Marked disparity in complication risk existed by age/sex (UTI: men 18–39 years 2.1%; women 80 years or older 22.5%). Prevalence of UTI (12.9%–9.7%) and pneumonia (3.8%–2.7%) declined, but that of ARF increased by ≈3-fold (4.8%–14%) over the period 2007–2019 (all p < 0.001). AMI (1.9%–3.1%), DVT (1.0%–1.4%), and PE (0.3%–0.8%) prevalence also increased ( p < 0.001), but that of sepsis and GIB remained unchanged over time. After multivariable adjustment, risk of all complications increased with increasing NIH Stroke Scale (pneumonia: prevalence rate ratio [PRR] 1.03, 95% CI 1.03–1.04, for each unit increase), but IV thrombolysis was associated with a reduced risk of all complications (pneumonia: PRR 0.80, 85% CI 0.73–0.88; AMI: PRR 0.85, 95% CI 0.78–0.92; and DVT PRR 0.87, 95% CI 0.78–0.98). Mechanical thrombectomy was associated with a reduced risk of UTI, sepsis, and ARF, but DVT and PE were more prevalent in MT hospitalizations compared with those without. All complications except UTI were associated with an increased risk of in-hospital mortality (sepsis: PRR 1.97, 95% CI 1.78–2.19). Discussion: Infectious complications declined, but noninfectious complications increased after AIS admissions in the United States in the last decade. Utilization of IV thrombolysis is associated with a reduced risk of all complications.